1997
DOI: 10.1093/genetics/147.1.305
|View full text |Cite
|
Sign up to set email alerts
|

Mu Element-Generated Gene Conversions in Maize Attenuate the Dominant Knotted Phenotype

Abstract: The knotted1 gene was first defined by dominant mutations that affect leaf morphology. The original allele, Kn1-O, results from a 17-kb tandem duplication. Mutator (Mu) insertions near the junction of the two repeats suppress the leaf phenotype to different degrees depending on the position of the insertion. The Mu insertions also increase the frequency of recombination at Kn1-O to create derivative alleles in which the Mu element and one copy of the repeat are lost. These derivatives are normal in appearance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Interestingly, interrupted GC was shown to generate truncated Mu elements in maize. The interruption was proposed to result from hybridizing direct repeats, upon which the gap resolution would lead to a deletion (Mathern and Hake, 1997). In our data we occasionally detected GCs associated with small deletions in recombinant molecules overlapping transposon related repeats.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Interestingly, interrupted GC was shown to generate truncated Mu elements in maize. The interruption was proposed to result from hybridizing direct repeats, upon which the gap resolution would lead to a deletion (Mathern and Hake, 1997). In our data we occasionally detected GCs associated with small deletions in recombinant molecules overlapping transposon related repeats.…”
Section: Discussionsupporting
confidence: 47%
“…Furthermore, the involvement of tomato transposable elements as drivers of meiotic recombination cannot be ruled out, since we observed putative GC in recombinant molecules overlapping with repeats and transposon copies. Previously, meiotic recombination and GC induced by the Mutator (Mu) transposon in maize, resulted in deletions affecting gene function of the knotted 1 gene (Mathern and Hake, 1997). A study on the trans-acting regulatory MuDR transposon revealed increasing GC and intragenic meiotic recombination in the vicinity of a nonautonomous Mu transposon (Yandeau-Nelson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This targeting tendency for Mu elements leads to frequent insertions in the 5′-untranslated region (UTR) and upstream regulatory sequences of genes where they can alter expression without disrupting coding sequences ( 13 , 14 , 44 ). Mu insertions in or near genes can have diverse effects, including increased or decreased gene expression ( 22 , 45 ) along with increased rates of recombination and gene conversion ( 46 , 47 ). These impacts contrast with the highly abundant retrotransposons, which do not preferentially target genic regions and appear to be recombinationally inert ( 48 50 ).…”
mentioning
confidence: 99%
“…Furthermore, the involvement of tomato transposable elements as drivers of meiotic recombination cannot be ruled out, since we observed putative GC in recombinant molecules overlapping with repeats and transposon copies. Previously, meiotic recombination and GC induced by the Mutator (Mu) transposon in maize, resulted in deletions affecting gene function of the knotted 1 gene (Mathern and Hake, 1997). A study on the trans-acting regulatory MuDR transposon revealed increasing GC and intragenic meiotic recombination in the vicinity of a nonautonomous Mu transposon (Yandeau-Nelson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%